2016
DOI: 10.1182/blood-2015-11-680199
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing reveals recurrent germ line variants in patients with familial Waldenström macroglobulinemia

Abstract: Familial aggregation of Waldenström macroglobulinemia (WM) cases, and the clustering of B-cell lymphoproliferative disorders among first-degree relatives of WM patients, has been reported. Nevertheless, the possible contribution of inherited susceptibility to familial WM remains unrevealed. We performed whole exome sequencing on germ line DNA obtained from 4 family members in which coinheritance for WM was documented in 3 of them, and screened additional independent 246 cases by using gene-specific mutation se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Nearly 30 novel susceptibility genes have been identified using various forms of DNA sequencing in the last five years. Some of these novel genes are listed in Table 2 1824 while others were summarized in a previous review 25 . Examples include variants in the POLE gene in colorectal cancer 26 or variants in the promoter region of TERT in familial and sporadic melanoma 27 .…”
Section: Novel Genomic Approaches To Cancer Preventionmentioning
confidence: 99%
“…Nearly 30 novel susceptibility genes have been identified using various forms of DNA sequencing in the last five years. Some of these novel genes are listed in Table 2 1824 while others were summarized in a previous review 25 . Examples include variants in the POLE gene in colorectal cancer 26 or variants in the promoter region of TERT in familial and sporadic melanoma 27 .…”
Section: Novel Genomic Approaches To Cancer Preventionmentioning
confidence: 99%
“…Authors have also demonstrated the 100% occurrence of the variant in WM patients with family history, [20] findings also confirmed more recently in a separate series of studies reporting on the role of LAPTM5 and HCLS1 germline variants in WM patients with coinheritance for WM. [24] From a clinical point of view, patients who were homozygous for MYD88 L265P presented with a longer mean interval since the diagnosis of WM was made; no differences in terms of other clinical features and laboratory findings were observed between homozygosity and heterozygosity for this variant. [25] Authors have also characterized the functional role of this mutation and described how the MYD88 L265P variant confers WM cell proliferative advantage through NFκB (NFκB) activation (Figure 1A).…”
Section: Mutational Profiling In Wm Cells and Related Functional Sequmentioning
confidence: 99%
“…There have been other reports of germ line mutations of genes causing a predisposition to leukemia that have not been replicated or reported in additional kindreds. These include the duplication of ATG2B and GSKIP, which seems to predispose to MPNs 49 ; mutations in RBB6 associated with MPNs 50 ; mutations in ACD that cause a BMF syndrome 51 ; mutations in SRP72 that lead to MDS 52 ; mutations in LAPTM5 and HCLS1 that are associated with familial Waldenström macroglobulinemia 53 ; and mutations in SH2B3 that appear to predispose to ALL. 54 Subsequent work will determine the extent to which germ line mutations in these genes have implications outside of the reported families.…”
Section: Emerging Leukemia Predisposition Syndromesmentioning
confidence: 99%